The influence of personality traits towards quality pledge - Ma’amora, Hairunnisa; Achim, Nur’ain; Muhamad Yunus, Nor Sara Nadia; Hashim, Nurhazirah; Haque, A. K. M. Ahasanul (Elsevier, 2016)
Any organization ventures in the hospitality industry are required to maintain a quality service to achieve competitive advantages. As employee’s commitment plays an important role in ensuring a high-quality service, their commitments are influenced by their personality traits, as they are also known as emotional labour. The purpose of this study is to investigate the dominant personality traits in the company based on the Big Five Personality theory, to assess the level of employees’ commitment to service quality (quality pledge) and its relationship. A structured survey was implied, and 143 customer contact employees participated. From the data analysed, the results show that there is a very strong relationship between personality traits and employees’ quality pledge. Hence, it is recommended for future research to make a comparison between the effect of personality traits towards quality pledge on employee’s perspective and also customer’s perspectives.